2014
DOI: 10.1007/s00418-014-1281-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of cholecystokinin (CCK)-1 receptors in the pancreas, gallbladder, and stomach of mice

Abstract: Information concerning the cellular localization of cholecystokinin (CCK)-1 receptors has been discrepant and remained scanty at ultrastructural levels. The present immunohistochemical study at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…A recent paper found CCK1(A)R signaling via ␤-arrestin, extracellular signal-regulated protein kinase (ERK), the 90-kDa ribosomal S6 kinase (p90RSK), and Bad regulates the ␤-cell antiapoptotic effects of CCK in high-glucose conditions (44). The expression of CCK receptors in the pancreatic islet has been controversial, with several studies finding disparate results in different species and using different antibodies (5,11,23,25,28,43,48). There are many challenges with antibodies raised against G protein-coupled receptors, and sensitivity and specificity problems can lead to uncertainty in the results (10).…”
Section: E825mentioning
confidence: 99%
“…A recent paper found CCK1(A)R signaling via ␤-arrestin, extracellular signal-regulated protein kinase (ERK), the 90-kDa ribosomal S6 kinase (p90RSK), and Bad regulates the ␤-cell antiapoptotic effects of CCK in high-glucose conditions (44). The expression of CCK receptors in the pancreatic islet has been controversial, with several studies finding disparate results in different species and using different antibodies (5,11,23,25,28,43,48). There are many challenges with antibodies raised against G protein-coupled receptors, and sensitivity and specificity problems can lead to uncertainty in the results (10).…”
Section: E825mentioning
confidence: 99%
“…However, neither FXR agonist GW4064 nor Fex selective inducing intestinal FGF15 production was suppress the expression of Cyp7a1 in vitro, which indicating that LXR, but not FXR/FGF15 was the dominant transcriptional regulator of Cyp7a1 under the condition of CAV1 depletion [Gupta et al, ; Inagaki et al, ]. Cholecystokinin A receptor (CCKAR) [Konno et al, ], a major physiologic mediator of gallbladder smooth muscle contraction was also suppressed in lithogenic diet‐fed CAV1 −/− mice. Lack CCKAR may aggravate cholestasis, deteriorate gallbladder contraction, and hence accelerate gallstone formation [Miyasaka et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of rabbit anti-CCK antiserum to I cells in the duodenal epithelium and mucosal nerve plexus in the colon has been confirmed by immunostaining using the same antiserum, and the specificity of the antigen-antibody reaction in this study was confirmed by preincubation of the antiserum with the corresponding antigen. The CCKAR antibodies were raised in a rabbit and guinea pig, as reported previously (19). The specificity of these antibodies has been shown by the disappearance of the immunoreactivities in tissue sections from CCKAR-deficient mice.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent in situ hybridization for CCK. Procedures for fluorescent in situ hybridization have been detailed elsewhere (19). Briefly, frozen sections~30 m thick were prepared from the paraformaldehyde-fixed kidneys, followed by inactivation of endogenous peroxidases with 1% H 2O2 (wt/vol).…”
Section: Methodsmentioning
confidence: 99%